Testing mechanical structural characteristics of Al2O3 oxide ceramics resistant to sliding friction - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Al2O3 is hard oxide ceramics, chemically bioinert and with good sliding properties; it has found wide application in the design of engineering components. The aim of the paper was to apply the APS process with the change of plasma currents in order to produce Al2O3 layers of such structural and mechanical properties which will find application in the manufacture of biomedical coatings alone or in combination with hydroxyapatite (HA) on the surfaces of alloys used for making implants. The coating was deposited with a plasma current of 700, 800 and 900 A. The mechanical properties of coatings were tested using the Pratt & Whitney standard. The shape of the surface of powder particles and the coating surface were examined by SEM. The metallographic analysis of the inner layers was carried out by light microscopy. The best structural and mechanical properties of the Al2O3 coating deposited with 900A were confirmed by testing the sliding properties of the coating deposited and polished to a mirror on the sealing ring paired with the graphite ring on the water brake.